Analysis of the 5G Architecture in Relation to the Non-Autonomous Option of the Global Mobile Ecosystem Association (GSMA).: Analysis of the 5G Architecture in Relation to the Non-Autonomous Option of the Global Mobile Ecosystem Association (GSMA). (Innovation & Development in Engineering and Applied Science, 2022)
The fifth generation of mobile technology represents a significant advance in the way data is communicated. The new economic development of countries will be based on this new technology that has arrived to transform and innovate the traditional way of doing everyday activities within the home, businesses, cities and governments. The present study aims to analyze the 5G architecture in relation to the non-autonomous option of the Global Mobile Ecosystem Association (GSMA). To perform the analysis, a systematic literature survey was conducted. The methods of analysis and synthesis and deductive and inductive were used to present the information collected on the 5G NSA architecture, the current state of telecommunications in Ecuador, and, the GSMA deployment options. Information was downloaded from official websites of organizations such as: GSMA, 5G Americas, ITU, 3GPPP, among others. Similarly, information was obtained from articles published in Google Scholar, Sciencie Direct, Scopus and IEEE. Of all the articles found, only 19 were selected. As a result, it was obtained that the 5G NSA is one of the best scenarios that mobile operators in Ecuador have for the deployment of 5G. Finally, through the analysis it was determined that the mobile operator CONECEL S.A. is the one that has the largest number of radio bases with 4G technology deployed in the country, therefore, it is more likely to have a high 5G coverage when deploying this technology.
Keywords: 5G; NSA; 5G architecture